Effects of fiber orientation and wall thickness on energy absorption characteristics of carbon-reinforced composite tubes under different loading conditions. (1st October 2016) - Wang, Yifan; Feng, Jiusheng; Wu, Jianghao; Hu, Dayong
Abstract: The collapse characteristics and energy absorption capability of G827/5224 composite tubes with different fiber orientation and wall thickness were studied under axial quasi-static and impact crushing conditions. The effects of fiber orientation, wall thickness and loading conditions on the crushing mode and energy absorption capability were discussed in detail. The experimental results showed that all tubes deform in a similar brittle fracturing crushing mode. In impact tests, smaller debris were generated and ejected from tube wall as compared to quasi-static tests. The fiber orientation and wall thickness were found to have significant influences on energy absorption performance. This demonstrated that the energy absorption capability could be improved by selecting proper fiber orientation and wall thickness. The energy absorption capability was also found to reduce remarkably under impact crushing condition in comparison with quasi-static crushing condition.